2008
DOI: 10.21273/horttech.18.1.13
|View full text |Cite
|
Sign up to set email alerts
|

WholeTree Substrates Derived from Three Species of Pine in Production of Annual Vinca

Abstract: The objective of this study was to evaluate the potential for use of container substrates composed of processed whole pine trees (WholeTree). Three species [loblolly pine (Pinus taeda), slash pine (Pinus elliottii), and longleaf pine (Pinus palustris)] of 8- to 10-year-old pine trees were harvested at ground level and the entire tree was chipped with a tree chipper. Chips from each tree species w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 11 publications
(11 reference statements)
1
28
0
Order By: Relevance
“…Research by Wehtje et al (2009) evaluated efficacy of prodiamine, flumioxazin, and isoxaben applications on crabgrass, eclipta, and spotted spurge, respectively, in standard pine bark and alternative wood-based substrates. Alternative substrates evaluated included clean chip residual and WholeTree, both wood-based forestry byproducts developed from different portions of pine trees Fain et al, 2008). Results showed that weed control was similar between the pine bark substrate and two alternatives when label rates of the herbicides were applied.…”
Section: Effect Of Production Practices On Weedmentioning
confidence: 99%
“…Research by Wehtje et al (2009) evaluated efficacy of prodiamine, flumioxazin, and isoxaben applications on crabgrass, eclipta, and spotted spurge, respectively, in standard pine bark and alternative wood-based substrates. Alternative substrates evaluated included clean chip residual and WholeTree, both wood-based forestry byproducts developed from different portions of pine trees Fain et al, 2008). Results showed that weed control was similar between the pine bark substrate and two alternatives when label rates of the herbicides were applied.…”
Section: Effect Of Production Practices On Weedmentioning
confidence: 99%
“…Wright et al (2006) and Jackson (2008) also evaluated the growth of numerous woody nursery species in a PTS produced from ground pine logs (including the bark; %90% wood and 10% bark) compared with 100% PB. Fain et al (2008aFain et al ( , 2008b) manufactured a PTS by chipping and grinding freshly harvested 8-to 10-year-old pine trees, including the wood, bark, limbs, and needles. They reported that herbaceous plants grown in PTS were smaller than plants grown in 100% PB, but that growth index and visual quality of the plants were similar for both substrates.…”
mentioning
confidence: 99%
“…Growth differences in these studies were attributed to lower nutrient levels in the PTS resulting from either leaching or microbial immobilization of applied nutrients. Fain et al (2008) manufactured a PTS (referred to as WholeTree) by chipping and grinding freshly harvested 8-to 10-year-old pine trees including the wood, bark, limbs, and needles. They reported that vinca (Catharanthus roseus L.) grown in PTS were smaller than plants grown in 100% PB, but that growth index and visual quality of the plants were similar for both substrates.…”
mentioning
confidence: 99%